Shakespeare and audience in practice - Purcell, Stephen (New York : Basingstoke, Hampshire, 2013)
What do audiences do as they watch a Shakespearean play? What makes them respond in the ways that they do? Exploring the practice of being a modern Shakespearean audience, Stephen Purcell examines a wide range of theatrical production, surveys some of the most influential ideas about spectatorship in contemporary performance studies, and analyses how both modern theatre practitioners and the play texts themselves positive audiences in particular ways. Innovative and insightful, this book includes detailed case studies of two modern productions, a collaborative debate section, and suggestions for practical exercises and further reading. Book jacket
What do audiences do as they watch a Shakespearean play? What makes them respond in the ways that they do? This book examines a wide range of theatrical productions to explore the practice of being a modern Shakespearean audience. It surveys some of the most influential ideas about spectatorship in contemporary performance studies, and analyses the strategies employed both in the texts themselves and by modern theatre practitioners to position audiences in particular ways.
Includes bibliographical references (pages 177-188) and index
Keywords: Shakespeare, William, -- 1564-1616 -- Dramatic production; Theater audiences